(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The purpose of this study is to the view to have a full concept of the history, antiquity,geography, topography and the connected topics involving the Kangra, its fort and its kings during theancient and mediaeval times. The major purpose of the present study is to establish the concerns andattempt an answer to the connected challenges. Before entering into details, it would be necessary hereto know about the geography, terrain and history of Himachal Pradesh, where the famed Kangra fort stillstands in its damaged condition.The fort of Rangra, which is now a forlorn mound of ruins, has longbeen regarded as inaccessible by Kangra monarchs. Up till the year 1620, Nagarkot was the seat ofKangra’s government and a part of Jalandhar’s empire. No archaeologist working in the Kangra regioncan avoid the topic of the present settlement’s general antiquity. The locals are extremely proud of thearea’s historical significance and never weary of bragging about their most ancient palace in the entireregion they call home. Seeing the fort from above and listening to the wind and water babbling in theBanganga defile below, one can’t help but rue the fact that so little is known about one of the country’smost remarkable structural remnants, set in an island-like mound created by Banganga and Manjhirivers. It still stands today as an impregnable castle, preserving several episodes from its illustriouspast.